Black Support of Neoliberal School Choice and the Politics of Black Democratic Empowerment. Issue 2 (21st July 2022) - Wheeler‐Bell, Quentin
Abstract: In Market Movements, Tom Pedroni argues that educational progressives often analyze neoliberal school choice policies by highlighting the negative impact such policies have upon Blacks. Implicit in this approach is the assumption that all Blacks should oppose neoliberalism. This assumption prevents scholars from investigating why African Americans increasingly do support neoliberal choice policies. Deep disagreements exist within the African American community over why Blacks are oppressed and how to understand their oppression, the nature of their disadvantages, and the remedies to such problems. And these disagreements affect why Blacks might support neoliberal school choice policies. In this paper, Quentin Wheeler‐Bell goes beyond explaining why deep disagreements exist within the Black public sphere and develops a critical theory of Black democratic empowerment. First, he provides a brief sociohistorical analysis of racial oppression, highlighting how domination has distorted and repressed debates within the Black public sphere, thus lending support to neoliberal choice policies. Second, he recovers and reconstructs four Black philosophical perspectives — (1) disillusioned Black liberals, (2) modern Black nationalists, (3) Black Marxists, and (4) Black egalitarians — and explains if and how they might be pulled into an alliance with neoliberal policies. Finally, he develops a critical theory of Black democratic empowerment that captures the reasonable insights from the abovementioned perspectives while avoiding the perils of neoliberal school choice.